2020
DOI: 10.3390/dj8040118
|View full text |Cite
|
Sign up to set email alerts
|

Communication, Trust and Dental Anxiety: A Person-Centred Approach for Dental Attendance Behaviours

Abstract: Effective communication forges the dentist-patient treatment alliance and is thus essential for providing person-centred care. Social rank theory suggests that shame, trust, communication and anxiety are linked together, they are moderated by socio-economic position. The study is aimed to propose and test an explanatory model to predict dental attendance behaviours using person-centred and socio-economic position factors. A secondary data analysis was conducted on a cross-sectional representative survey of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…The socioeconomic variables (education and income) were left out of the regression analysis due to their lack of significant impact in the first trial model (not reported). However, it is known that socioeconomic status impacts oral health [ 72 ], and there is evidence that social class affects communication and trust in the patient-caregiver relationship [ 73 ]. Dental anxiety has a multifactorial aetiology; hence, effect sizes for the single variables are not expected to be high.…”
Section: Discussionmentioning
confidence: 99%
“…The socioeconomic variables (education and income) were left out of the regression analysis due to their lack of significant impact in the first trial model (not reported). However, it is known that socioeconomic status impacts oral health [ 72 ], and there is evidence that social class affects communication and trust in the patient-caregiver relationship [ 73 ]. Dental anxiety has a multifactorial aetiology; hence, effect sizes for the single variables are not expected to be high.…”
Section: Discussionmentioning
confidence: 99%
“…Such an active engagement of a short questionnaire assessment, as part of good communication between patients and dental staff, may confer a beneficial effect for relieving patients’ anxiety [ 33 ]. Furthermore, results from a cross-sectional survey in the UK revealed that dental anxiety is associated with patients’ trust in dentists and their feelings of shame about their oral condition [ 34 ]. Consistently, our findings revealed that higher dental anxiety was associated with subjects’ perception of the lack of skills and empathy of dentists.…”
Section: Discussionmentioning
confidence: 99%
“…The CEDAM-8 could therefore act as a valuable clinical tool that can aid effective communication and promote collaboration between the child, parent and dental team. Positive patient-dentist interactions are fundamental to the delivery of patientcentred care and play an important role in promoting regular dental attendance [25].…”
Section: Discussionmentioning
confidence: 99%